2022
DOI: 10.21203/rs.3.rs-1841990/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMEM201 overexpression is associated with tumor progression and unfavorable prognosis in hepatocellular carcinoma

Abstract: Background More and more evidences suggest there was a relationship between nuclear envelope and tumor development, but the functional contributions of TMEM201 remain largely unidentified. Objective This study aimed to explore the TMEM201 mRNA expression and its potential biologic functions in hepatocellular carcinoma (HCC) patients. Methods Expression array and clinical data were collected from the Cancer Genome Atlas (TCGA) database. TMEM201 expression data and its clinical information in HCC were confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The current study supported the previous reports that demonstrated the diagnostic potential of MCM2 for cervical cancer. On the other hand, the KPNA2 marker was recorded as prognostic marker for cervical squamous cell carcinoma and overexpression of KPNA2 was related with poor prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study supported the previous reports that demonstrated the diagnostic potential of MCM2 for cervical cancer. On the other hand, the KPNA2 marker was recorded as prognostic marker for cervical squamous cell carcinoma and overexpression of KPNA2 was related with poor prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the KPNA2 marker was recorded as prognostic marker for cervical squamous cell carcinoma and overexpression of KPNA2 was related with poor prognosis [40].…”
Section: Discussionmentioning
confidence: 99%